2016
DOI: 10.20341/gb.2015.017
|View full text |Cite
|
Sign up to set email alerts
|

Filling the North Sea Basin: Cenozoic sediment sources and river styles

Abstract: ABSTRACT. The history of the infilling of the North Sea is outlined, with particular focus on sediment sources and river inputs. In simple terms (for the detail is complex), these sources changed from domination by northwesterly sources from the Shetland area (Paleocene to Eocene), to a geographically more uniform basin-centred pattern, and then northerly input following Fennoscandian uplift (Oligocene and Neogene). Baltic inputs followed via an 'Eridanos (Baltic) River' (Miocene), with cold-climate coarser se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 105 publications
(156 reference statements)
1
52
0
Order By: Relevance
“…Geographical map of the present-day North Sea region with the superimposed thickness of Cenozoic sediment infill after Ziegler (1990) and the offshore sectors (dashed lines). The reconstructed different water sources (see Gibbard and Lewin, 2016) that influenced the Pliocene and early Pleistocene North Sea hydrography, including the freshwater supply of the Baltic River system, the RhineMeuse River system, and Atlantic surface waters, are indicated with blue arrows. The location of both boreholes A15-3 (UTM X 552567.1, Y 6128751.6) and A15-4 (UTM X 557894.4, Y 6117753.5) is marked by an asterisk; see Fig.…”
Section: B a L T I C R I V E R S Y S T E Mmentioning
confidence: 99%
“…Geographical map of the present-day North Sea region with the superimposed thickness of Cenozoic sediment infill after Ziegler (1990) and the offshore sectors (dashed lines). The reconstructed different water sources (see Gibbard and Lewin, 2016) that influenced the Pliocene and early Pleistocene North Sea hydrography, including the freshwater supply of the Baltic River system, the RhineMeuse River system, and Atlantic surface waters, are indicated with blue arrows. The location of both boreholes A15-3 (UTM X 552567.1, Y 6128751.6) and A15-4 (UTM X 557894.4, Y 6117753.5) is marked by an asterisk; see Fig.…”
Section: B a L T I C R I V E R S Y S T E Mmentioning
confidence: 99%
“…The pre‐Quaternary surface can be morphologically subdivided into three major planation surfaces (Marginal, Middle and Offshore Platforms), each bound by escarpments or slope breaks that cut across different Paleogene strata of varying resistance (De Batist, ; Liu, ; Mathys, ; De Clercq et al ., ) that were formed under marine to near‐coastal conditions (Gibbard and Lewin, ; Boulvain and Vandenberghe, ). This setting resulted in a lateral changing lithology composed of consolidated clays and sand‐silt‐clay layers locally containing sandstone layers (De Batist, ; Jacobs and De Batist, ; Le Bot et al ., ).…”
Section: Geomorphological – Stratigraphical Settingmentioning
confidence: 97%
“…The middle Miocene (late Langhian) palaeogeography of the North Sea Basin and surrounding areas, modified from Gibbard and Lewin (). The study area of Figure is indicated [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%